2003
DOI: 10.1109/tgrs.2002.808244
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the AIRS radiative transfer model

Abstract: The two main elements of the Atmospheric Infrared Sounder Radiative Transfer Algorithm (AIRS-RTA) are described in this paper: 1) the fast parameterization of the atmospheric transmittances that are used to perform the AIRS physical retrievals and 2) the spectroscopy used to generate the parameterized transmittances. We concentrate on those aspects of the spectroscopy that are especially relevant for temperature and water vapor retrievals. The AIRS-RTA is a hybrid model in that it parameterizes most gases on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
183
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(188 citation statements)
references
References 21 publications
0
183
0
Order By: Relevance
“…AIRS uses a physical algorithm for the retrieval of atmospheric profiles dependent on fast and accurate radiative transfer algorithm for computing clear-air radiances which uses approximately 300 channels to determine temperature, water, and ozone profiles [25]. The cross-track scanner of AIRS with 15 km resolution at nadir and 705 km orbital altitude, produces highly accurate global atmospheric profiles product twice every day [26,27].…”
Section: Multisensors Data Productsmentioning
confidence: 99%
“…AIRS uses a physical algorithm for the retrieval of atmospheric profiles dependent on fast and accurate radiative transfer algorithm for computing clear-air radiances which uses approximately 300 channels to determine temperature, water, and ozone profiles [25]. The cross-track scanner of AIRS with 15 km resolution at nadir and 705 km orbital altitude, produces highly accurate global atmospheric profiles product twice every day [26,27].…”
Section: Multisensors Data Productsmentioning
confidence: 99%
“…The N-T retrieval algorithm is applied to both AIRS and NAST-I data to minimize the impact of retrieval algorithm differences on the retrieval products. However, it should be noted that the forward radiative transfer models used differ in that the optimal spectral sampling (OSS) fast molecular radiative transfer model is used for the NAST-I retrieval Moncet et al, 2003) while the Stand-alone AIRS Radiative Transfer Algorithm (SARTA) is used for the AIRS retrieval (Strow et al, 2003). The A-T retrieval methodology uses eigenvector regression to obtain initial profiles as well (Goldberg et al, 2003;Susskind et al, 2003;Susskind et al, 2006).…”
Section: Retrieval Algorithmsmentioning
confidence: 99%
“…The RTM −1 (Zhou et al 2007(Zhou et al , 2009) used here only uses observed radiance and instrument random noise; no other 'truth' data from satellite or surface-based instruments or from numerical weather analysis/prediction models are utilized in assisting or constraining the retrieval products. The fast transmittance model used herein is a combination of the Stand-alone AIRS Radiative Transfer Algorithm (SARTA) Version 1.07 and the physically based cloud RTM based on the discrete ordinate radiative transfer (DISORT) calculations performed for a wide variety of cloud microphysical properties (Stamnes et al 1988, Yang et al 2001, Strow et al 2003. The studies presented here only deal with clear-sky conditions; therefore, DISORT (or the cloud radiative transfer) model error is not estimated.…”
Section: Analysis Demonstrationmentioning
confidence: 99%